Asteroseismology of 36 Kepler subgiants – II. Determining ages from detailed modelling. Issue 3 (15th May 2020) - Li, Tanda; Bedding, Timothy R; Christensen-Dalsgaard, Jørgen; Stello, Dennis; Li, Yaguang; Keen, Matthew A
ABSTRACT: Detailed modelling of stellar oscillations is able to give precise estimates for stellar ages, but the inferred results typically depend on the adopted model parameters used for the age inference. High-quality asteroseismic data with precise measurements of mixed modes are available for 36 Kepler subgiants. To obtain a handle on the robustness of the ages for these stars, we first study the dependencies of seismic ages on three model input parameters. We find that inferred ages do not change systematically with the helium fraction ( Y ) or the mixing-length parameter (αMLT ) but depend strongly on the metallicity ([ M / H ]) of the model. The results indicate that age estimates of subgiants have less model dependence and hence are more reliable than those of main-sequence stars or red giants. We then model individual oscillation frequencies of the same 36 Kepler subgiants, using observed metallicities, and obtain their ages with an average precision of ${\sim}15{{\ \rm per\ cent}}$ . The comparison with previous age estimates with different stellar codes or input physics shows good agreement (mostly within 2σ). We hence suggest that seismology-determined ages of subgiants are not greatly model dependent.